Carbohydrates in Chemistry and Biology 2000
DOI: 10.1002/9783527618255.ch41
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sugar Transporters

Abstract: The cellular loci for the production of secreted and membrane bound glycoproteins and glycolipids are the endoplasmic reticulum (ER) and the Golgi apparatus. Both compartments are sealed vesicular structures that require active in-and outward transport of metabolites that are substrates or products of catalytic reactions taking place at the luminal side. Studies on the secretory pathway carried out in the 1960s, together with the delineation of the steps involved in N-glycosylation in the 1970s, made the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In the protozoal parasite Leishmania donovani, which causes visceral leishmaniasis, a mannose-rich lipophosphoglycan (LPG) was shown to be important for virulence; one avirulent mutant, LPG2, has a defect in a GDP-mannose transporter (53). The C. elegans genome contains 16 NST-like proteins, of which only three have been described in detail (54). SQV-7, the null phenotype of which is embryonic lethal, is a transporter with multisubstrate specificity (28,55).…”
Section: Discussionmentioning
confidence: 99%
“…In the protozoal parasite Leishmania donovani, which causes visceral leishmaniasis, a mannose-rich lipophosphoglycan (LPG) was shown to be important for virulence; one avirulent mutant, LPG2, has a defect in a GDP-mannose transporter (53). The C. elegans genome contains 16 NST-like proteins, of which only three have been described in detail (54). SQV-7, the null phenotype of which is embryonic lethal, is a transporter with multisubstrate specificity (28,55).…”
Section: Discussionmentioning
confidence: 99%
“…In contradiction, a recent report has shown that the 21-residue peptide displayed only approximately 100% C3a activity in the ATPrelease assay as well as the ileum contraction assay (16). Previous results from Gerardy-Schahn et al (7) and Ambrosius etal. (8) indicated that flexible linear amphipathic molecules are potent biological agonists (e.g.…”
mentioning
confidence: 81%
“…In contrast to Leu75, Leu73 can be replaced by various non-charged amino acids without significant loss of activity (12,13). The replacement of Gly7J by Ala resulted in a two-fold higher activity (7,8). In contrast to former studies, which determined the C-terminal pentapeptide LGLAR (C3a 73-77) as active site, our recent work on very short C3a analogues has shown that the C-terminal tripeptide -LAR is sufficient to trigger ATP release from gp platelets (1 1, 12), if a hydrophobic potentiator (e.g.…”
mentioning
confidence: 92%
See 2 more Smart Citations